Resolution of fuzzy relational equations – Method, algorithm and software with applications - Peeva, K. (Information sciences, 2013)
Analytical methods and algorithms for inverse problem resolution of fuzzy linear systems of equations in some BL-algebras (Gödel algebra in case of max–min and min–max compositions, and Goguen algebra in case of max–product composition) are presented. Algorithms with software realization for solving fuzzy linear systems of equations are proposed. Applications include fuzzy optimization with fuzzy linear systems of equation constraint, fuzzy machines and covering problem.